2018
DOI: 10.1172/jci96165
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase N1 critically regulates cerebellar development and long-term function

Abstract: Increasing evidence suggests that synapse dysfunctions are a major determinant of several neurodevelopmental and neurodegenerative diseases. Here we identify protein kinase N1 (PKN1) as a novel key player in fine-tuning the balance between axonal outgrowth and presynaptic differentiation in the parallel fiber–forming (PF-forming) cerebellar granule cells (Cgcs). Postnatal Pkn1–/– animals showed a defective PF–Purkinje cell (PF-PC) synapse formation. In vitro, Pkn1–/– Cgcs exhibited deregulated axonal outgrowth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 61 publications
2
13
0
Order By: Relevance
“…Additionally, PKN1 is an effector protein kinase of Rho family GTPases, such as RhoA, RhoB, RhoC, and Rac 1, in mammalian tissues 713 . PKN1 is expressed ubiquitously and involved in various functions, including cell-cell adhesion 14,15 , cell migration 1619 , vesicle transport 20,21 , cell survival 2226 , cell cycle regulation 18,2731 , transcriptional regulation 3236 , tumorigenesis 19,32,33,37,38 , myogenic differentiation 39 , parallel fiber-Purkinje-cell synapse formation in the cerebellum 40 , and pyrin inflammasome formation 41,42 . In some cases, PKN1 reportedly plays important roles independent of its kinase activity, such as activation of phospholipase D1 43 , scaffolding for p38γ mitogen-activated protein kinase signaling 44 , and increasing the survival of cardiac muscle cells following ischemia/reperfusion 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, PKN1 is an effector protein kinase of Rho family GTPases, such as RhoA, RhoB, RhoC, and Rac 1, in mammalian tissues 713 . PKN1 is expressed ubiquitously and involved in various functions, including cell-cell adhesion 14,15 , cell migration 1619 , vesicle transport 20,21 , cell survival 2226 , cell cycle regulation 18,2731 , transcriptional regulation 3236 , tumorigenesis 19,32,33,37,38 , myogenic differentiation 39 , parallel fiber-Purkinje-cell synapse formation in the cerebellum 40 , and pyrin inflammasome formation 41,42 . In some cases, PKN1 reportedly plays important roles independent of its kinase activity, such as activation of phospholipase D1 43 , scaffolding for p38γ mitogen-activated protein kinase signaling 44 , and increasing the survival of cardiac muscle cells following ischemia/reperfusion 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Considering that many synapses are not covered by glial processes in the hippocampus 44 , 45 , EAAT3 may be more important in synapses specifically in the developing hippocampus. A recent study suggested a role of PKN1 in development of cerebellar circuits 24 . In this study we identify PKN1 as an important promoter of synapse maturation through upregulation of neuronal glutamate transporters and inhibition of mGluR-dependent synapse silencing in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…PKN has been implicated in cell proliferation or metastasis of many types of tumor including prostate and bladder cancers, and PKN inhibitors may treat them 20 , 23 . Very recently, PKN1 has been reported to be involved in axonal outgrowth and presynaptic differentiation of parallel fibers of cerebellar granule cells 24 ; however, the physiological roles of PKN in the brain have not been fully clarified yet. Therefore, we investigated the function of PKN1 in the hippocampus by generating PKN1a knockout (KO) mice (Supplementary Fig.…”
Section: Introductionmentioning
confidence: 99%
“…PKN1 (protein kinase N1) is a stress-responsive kinase and a member of the protein kinase novel (PKN) family also known as protein kinase C-related kinases (PRKs) [20,21]. The interaction of Rho with PKN1 induces a conformational change in PKN1 leading to activation loop phosphorylation by 3-Phosphoinositide-Dependent Kinase-1(PDK1) on Thr 774 in the case of human PKN1 (Thr 778 in mouse/rat) which is necessary for the catalytic activation of PKN1/2 14 and critical for the stability of the protein [22,23]. PKN1 is shown to provide a basal cardioprotective function in the face of I/R injury [24].…”
Section: Discussionmentioning
confidence: 99%